A novel family of layered double hydroxides - [MAl4(OH)(12)](NO3)(2)center dot xH(2)O (M = Co, Ni, Cu, Zn) - Fogg, A; Williams, G; Chester, R; O'Hare, D (2004)
A class of layered double hydroxides with the layer composition [MAl 4(OH)12](NO3)2·xH 2O, where M = Zn, Cu, Ni and Co, has been synthesised for the first time and its anion exchange chemistry explored. These materials are related to the minerals chalcoalumite, mbobomkulite and nickelalumite (see M. Fleischer, R. G. Burns, L. J. Cabri, C. A. Francis and A. Pabst, Am. Miner., 1982, 67, 413).